2023
DOI: 10.30574/gscarr.2023.14.2.0040
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and clinical characteristics of women with unsafe abortion in south-western Nigeria

Abstract: Background: Unsafe abortion is within the five leading causes of maternal mortality in sub Saharan Africa. For every one death related to unsafe abortion, about 25 more women suffer significant morbidity from complications of abortion The aim is to highlight their socio-demographic and clinical characteristics of women with unsafe abortion. Methodology: This was a 5-year retrospective cross-sectional study of 84 women managed for complications of unsafe abortion, at the Federal Teaching Hospital Ido-Ekiti, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In Nigeria, despite the outlaw of induced abortion, abortions remain very high for 15 to 19-year-old girls due to unintended pregnancy [ 18 , 19 ]. A southwestern Nigerian study ( n = 84) found that 39.3% of those with secondary education had unsafe abortion [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, despite the outlaw of induced abortion, abortions remain very high for 15 to 19-year-old girls due to unintended pregnancy [ 18 , 19 ]. A southwestern Nigerian study ( n = 84) found that 39.3% of those with secondary education had unsafe abortion [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, despite the outlaw of induced abortion, abortions remain very high for 15 to 19-year-old girls due to unintended pregnancy [ 18 , 19 ]. A southwestern Nigerian study ( n = 84) found that 39.3% of those with secondary education had unsafe abortion [ 19 ]. Child marriage contribution to adolescent pregnancy in Nigeria [ 16 ] is exacerbated by other interpersonal level factors such as cultural norms that allows household decision makers to break defilement laws with little or no consequences [ 7 , 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%